The Impact of Macro-Economic and Financial Variables on Commercial Bank Deposits in Nepal - Pun, Kalpana (The Lumbini Journal of Business and Economics, 2021)
The main objective of this study is to examine the potential impact of economic and financial variables on total deposit in Nepalese context by using quarterly time series data that spanned from 2009 Q4 to 2020 Q3. This study investigated using unit root (stationary) test, Johansen co-integration, and Granger causality test to analyze long-run association and causal relationship among variables under consideration. The study finds the empirical evidence of long-run integration and causality of economic and financial variables and bank deposits in Nepal. The result indicated bi-directional link between total deposit and inflation, inflation and money supply, and found uni-direction relation among some explanatory variables. Interestingly, the causation is found with a lag of 2 years. Hence, government should focus on such macro-economic and financial variables in order to maintain the economic and financial diplomacy of Nepal. This finding holds practical implication for policy maker, depositors, investors, and financial market analyst.